2020
DOI: 10.2215/cjn.13371019
|View full text |Cite
|
Sign up to set email alerts
|

Response to First Course of Intensified Immunosuppression in Genetically Stratified Steroid Resistant Nephrotic Syndrome

Abstract: Background and objectivesIntensified immunosuppression in steroid-resistant nephrotic syndrome is broadly applied, with disparate outcomes. This review of patients from the United Kingdom National Study of Nephrotic Syndrome cohort aimed to improve disease stratification by determining, in comprehensively genetically screened patients with steroid-resistant nephrotic syndrome, if there is an association between response to initial intensified immunosuppression and disease progression and/or post-transplant rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 49 publications
1
39
0
Order By: Relevance
“…Approximately 60% of steroid-resistant patients may respond to ciclosporin or tacrolimus at moderate doses with reduced proteinuria and slower or halted CKD progression 196 . A genetic cause is usually not found in these patients 65,67,156 . As relapse is frequent after the withdrawal of these drugs 196 , prolonging treatment for 1-3 years after remission is achieved is advisable 157 .…”
Section: Srnsmentioning
confidence: 94%
See 2 more Smart Citations
“…Approximately 60% of steroid-resistant patients may respond to ciclosporin or tacrolimus at moderate doses with reduced proteinuria and slower or halted CKD progression 196 . A genetic cause is usually not found in these patients 65,67,156 . As relapse is frequent after the withdrawal of these drugs 196 , prolonging treatment for 1-3 years after remission is achieved is advisable 157 .…”
Section: Srnsmentioning
confidence: 94%
“…Genetic variants in >50 nuclear and mitochondrial genes have been associated with FSGS and most cases are resistant to steroid therapy 65,67,156 . Inheritance patterns include autosomal recessive, autosomal dominant and sex-linked.…”
Section: Anasarcamentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, a genetic diagnosis can have strong implications for patient management and should always be considered in earlyonset disease, particularly in the presence of a clear family history. For example, most genetic forms of steroidresistant nephrotic syndrome may not respond to immunosuppression therapy (69). Therefore, a positive finding may spare a patient from unwanted complications from this therapy (70).…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…Studies have shown that a higher proportion of genetictesting-negative patients achieve remission with immunosuppressive agents than those with genetic FSGS [26,27]. This nding suggests that those who respond to immunosuppressants are likely to have primary FSGS or CFs-mediated FSGS [26,27]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 84%